Being a nurse: The lived experience of registered nurses educated in an accelerated second degree bachelor of science in nursing program. - Hennessy, Lisa L (Being a Nurse: The Lived Experience of Registered Nurses Educated in an Accelerated Second Degree Bachelor of Science in Nursing Program, 2012)
This research was an interpretive phenomenological study aimed at exploring the lived experience of nurses educated in accelerated second degree bachelor of science in nursing (ASD-BSN) programs. The method used to investigate the phenomenon was based on the philosophy of Martin Heidegger, as articulated by Patricia Benner (1994) and Marlene Zichi Cohen, David L. Kahn, and Richard H. Steeves (2000). The sample for this study was purposive in nature and drawn from registered nurses practicing in the southwestern United States who were educated in an ASD-BSN program. The results included the emergence of four major themes and a model of ASD-BSN nursing practice. The themes which emerged were the Headwaters, Tributaries and Turbulence, the Rolling River, and the Delta. This study adds to professional nursing's understanding of how ASD-BSN prepared nurses experience their career as professional nurses in terms of their motivation to become nurses, how they experience their nursing practice, and how they interact with the nursing profession. Based on this understanding, indications for ASD-BSN education, employment orientation, management, and career progression were identified.